BAZNAS Kabupaten Purbalingga Dalam Membangun Sinergi Antar Lembaga - Maulani, Dita Dwi; Suyuti, Muh Hikamudin (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The percentage of poverty in Indonesia in 2024 reached 24.06%, thus encouraging the government to carry out various initiatives for poverty alleviation, one of which is through the National Amil Zakat Agency (BAZNAS). BAZNAS functions as a non-structural government institution that is fully committed to the implementation of zakat at the national level, where BAZNAS is formed at the provincial and regional levels to carry out tasks throughout the region. As an obligation that must be done for Muslims, zakat plays an important role in fostering social justice and welfare. The purpose of this study is to understand the innovations used by BAZNAS Purbalingga Regency in developing partnerships with various organizations to increase zakat, infaq, and sadaqah (ZIS) payments. The research method used is a qualitative approach with a descriptive focus involving observation, literature, and interviews. The results showed that BAZNAS Purbalingga implemented innovations in cooperation with local government agencies, cooperation with financial institutions, cooperation with the business world, cooperation with educational institutions, and cooperation with community organizations. Through this innovation, BAZNAS Purbalingga aims to increase public trust in the implementation of zakat while optimizing the distribution and utilization of zakat by the wider community. The synergy is expected to increase the value of zakat for mustahik and support poverty alleviation efforts in the region.